POSSIBLE SOURCES OF BETTI KATZENSTEIN'S TEACHING STRATEGY - Borsato, Claudia; Cunha, Marcus Vinicius da [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2016)
This work is based on a previous research that analyzed a series of articles published by Betti Katzenste between 1947 and 1948 in Rio de Janeiro's Folha da Manha Newspaper Psychological Clinic column, Women's Notebook section. That research revealed that some items were prepared in the form of dialogues between two fictional characters - Dona Anastacia, a woman of little education, and a psychologist, in such a way in which the author could instruct readers about rhetorical strategies of persuasion. This work also focuses on Katzenstein's possible sources of inspiration concerning teaching strategy. It analyzes the publications of the Brazilian Journal of Pedagogical Studies between 1944 and 1948 in search of matters relating to teaching methodologies as well as two books (The Theatre of Spontaneity from 1923 and Psychodrama from 1946) written by Jacob Levy Moreno, creator of Psychodrama.
Keywords: History of Education; History of Psychology; Teaching St rategies; Persuasion; Rhetoric